Porous material with desulfurization and denitrification functions as well as preparation method and application thereof

The preparation of porous materials composed of Si, Al and Cu by hydrothermal crystallization has solved the shortcomings of the existing adsorption and desulfurization and denitrification technology in terms of adsorption performance, and achieved efficient desulfurization and denitrification effects.

CN119838556AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311348679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

The existing adsorption desulfurization and nitrogen removal technology has problems in terms of adsorption performance of active components, easy aggregation, and poor ammonia nitrogen removal effect.

Method used

By hydrothermal crystallization of crystallized raw materials containing silicon, aluminum and active metal sources, a porous material composed of Si, Al and Cu was prepared, and the adsorption properties of this material were used to achieve desulfurization and nitrogen removal.

Benefits of technology

The porous material exhibits high efficiency in desulfurization and nitrogen removal, with high desulfurization and nitrogen removal, good diffusion performance and difficult to accumulate. The preparation process is simple, which avoids complicated post-treatment processes and saves manpower and material resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838556A_ABST
    Figure CN119838556A_ABST
Patent Text Reader

Abstract

The invention relates to the field of raw material purification, and discloses a porous material with desulfurization and denitrification functions as well as a preparation method and application thereof. The porous material disclosed by the invention is excellent in desulfurization and denitrification performance and can be prepared by adopting a one-step synthesis method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of raw material purification, and in particular to a porous material with desulfurization and denitrification functions, and a preparation method and application thereof. Background Art

[0002] In recent years, with the improvement of energy conservation and environmental protection requirements and the improvement of oil quality requirements, oil refining companies have stepped up their research on desulfurization and denitrification technologies while upgrading their equipment and oil products. SO x and NO x It not only contributes to the formation of acid rain, but also promotes the emission of particulate matter. The current desulfurization and denitrification technologies are mainly divided into two methods: reaction and adsorption. Although reactive desulfurization and denitrification have the advantages of high yield, the entire process is relatively long, the energy consumption is also relatively high, and the octane number loss is relatively large. Adsorption desulfurization and denitrification use the complexation, van der Waals force or chemical reaction between sulfur or nitrogen and the adsorbent to remove. It has the advantages of high removal depth, easy regeneration, low cost, and easy operation. However, there are still problems in terms of adsorption performance (such as uneven dispersion of active components, easy aggregation, poor ammonia nitrogen removal effect, etc.).

[0003] Therefore, it is of great significance to develop a porous material for desulfurization and denitrification with good adsorption performance, simple preparation process and environmental friendliness. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a porous material with desulfurization and denitrification functions and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a method for preparing a porous material with desulfurization and denitrification functions, the preparation method comprising: hydrothermally crystallizing a crystallization raw material containing a silicon source, an aluminum source and an active metal source, wherein the weight ratio of the silicon source calculated as SiO2, the aluminum source calculated as Al2O3, and the active metal source calculated as metal oxide is 1:0.001-2.5:0.01-0.3, and the active metal source is selected from at least one of a Group VIII metal source, a Group IB metal source and a Group IIB metal source.

[0006] A second aspect of the present invention provides a porous material having desulfurization and denitrification functions.

[0007] The third aspect of the present invention provides a method for desulfurization and denitrification, which comprises: contacting the material to be desulfurized and denitrified with the porous material as described above.

[0008] The fourth aspect of the present invention provides the use of the porous material as described above in desulfurization and denitrification.

[0009] Through the above technical scheme, the porous material of the present invention can achieve desulfurization and denitrification by adsorption, and has high desulfurization and denitrification rates, good diffusion performance, and is not easy to aggregate. Under similar performance conditions, compared with traditional adsorbents, the one-step synthesis method is used to avoid complicated post-processing processes and save a lot of manpower and material resources. The preparation process of the present invention is simple, the content of active components is small, the composition is easy to control, and it is easy to scale up. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a scanning electron microscope photograph of a desulfurization and denitrification dual-functional porous material obtained according to a preferred embodiment of the present invention;

[0011] Figure 2 This is the XRD spectrum of the desulfurization and denitrification dual-functional porous material obtained according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] The present invention provides a method for preparing a porous material with desulfurization and denitrification functions, characterized in that the preparation method comprises: hydrothermally crystallizing a crystallization raw material containing a silicon source, an aluminum source and an active metal source, wherein the weight ratio of the silicon source calculated as SiO2, the aluminum source calculated as Al2O3, and the active metal source calculated as metal oxide is 1:0.001-2.5:0.01-0.3.

[0014] Preferably, the weight ratio of the aluminum source calculated as Al2O3 to the silicon source calculated as SiO2 is 0.005-2, such as 0.005, 0.01, 0.02, 0.05, 0.07, 0.08, 0.09, 0.1, 0.5, 1, 1.5, 2 or any value or range therebetween.

[0015] Preferably, the weight ratio of the active metal source calculated as metal oxide to the silicon source calculated as SiO2 is 0.02-0.25, such as 0.02, 0.05, 0.09, 0.1, 0.15, 0.2, 0.22, 0.23, 0.24, 0.25 or any value or range therebetween.

[0016] In the present invention, the silicon source can be selected from the common substances in the art that can provide silicon elements, for example, the silicon source can be selected from at least one of silicon oxide, silicic acid, silicate, silicate and siloxane. Preferably, the silicon source is selected from at least one of silica sol, white carbon black, tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate and dimethylsiloxane.

[0017] In the present invention, the aluminum source can be selected from the common substances in the art that can provide aluminum elements, for example, the aluminum source can be selected from at least one of aluminum alkoxide, aluminum oxide, aluminum hydroxide, aluminum salt and aluminate. Preferably, the aluminum source is selected from at least one of aluminum isopropoxide, pseudo-boehmite (AlOOH·nH2O, n=0.08-0.62), aluminum oxide (Al2O3), aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum sulfate and sodium aluminate.

[0018] In the present invention, the active metal source can be selected from substances that are common in the art and can provide at least one of Group VIII metal elements, Group IB metal elements and Group IIB metal elements (especially at least one of Cu, Zn and Fe), for example, can be selected from metal salts. In order to obtain a porous material with better performance, the active metal source is selected from at least one of a copper source, a zinc source and an iron source. Among them, the copper source, the zinc source and the iron source are substances that can provide copper, zinc and iron elements, respectively. The copper source can be selected from at least one of copper salts (especially inorganic copper salts). The zinc source can be selected from at least one of zinc salts (especially inorganic zinc salts). The iron source can be selected from at least one of iron salts (especially inorganic iron salts). More preferably, the active metal source is selected from at least one of copper nitrate, copper carbonate and zinc nitrate.

[0019] In the present invention, in order to obtain a porous material with better desulfurization and denitrification effects, the crystallization raw material may further contain an alkali source in the form of OH - The weight ratio of the alkali source in terms of SiO2 to the silicon source in terms of SiO2 is less than or equal to 3, preferably 0.01-2.5, such as 0.01, 0.02, 0.05, 0.1, 0.2, 0.25, 0.3, 0.5, 1, 1.5, 2, 2.5 or any value or range between the above values. The alkali source can be selected from substances that can be hydrolyzed to produce hydroxyl groups commonly found in the art, preferably, the alkali source is selected from alkali metal hydroxides and / or ammonia, more preferably at least one of sodium hydroxide, potassium hydroxide and ammonia. In the present invention, ammonia is usually used in the form of aqueous ammonia.

[0020] In the present invention, the amount of water in the crystallization raw material is such that the weight ratio of water to silicon source calculated as SiO2 is less than or equal to 300, preferably 0.001-280, such as 0.001, 0.01, 0.1, 1, 10, 12, 15, 20, 100, 200, 250, 280 or any value or range between the above values.

[0021] In the present invention, in order to obtain a porous material with better desulfurization and denitrification effects, the crystallization raw material preferably further contains an additive, and the weight ratio of the additive to the silicon source in terms of SiO2 is less than or equal to 0.1, preferably 0.01-0.1, and more preferably 0.02-0.08, such as 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08 or any value or range between the above values. The additive can be selected from at least one of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymers, polyethylene glycol and long-chain alkyl trimethyl ammonium halide. In order to obtain a porous material with better desulfurization and denitrification effects, preferably, the additive is selected from polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymers (the average molecular weight is preferably between 1500-12000), structures such as CH3(CH2) n N + (CH3)3X - At least one of the long-chain alkyltrimethylammonium halides shown (n is preferably an integer of 8-18; X represents a halogen, preferably Cl or Br).

[0022] In a preferred embodiment of the present invention, the conditions for the hydrothermal crystallization include: a temperature of 70-220°C, preferably 90-200°C, and more preferably 140-160°C.

[0023] In a preferred embodiment of the present invention, the hydrothermal crystallization conditions further include: a time of 0.1-7 days, preferably 0.2-5 days, and more preferably 1-2 days.

[0024] In the present invention, the method may further include aging the crystallization raw material before hydrothermal crystallization, and the aging conditions include: temperature of 15-45°C (room temperature), more preferably 20-30°C, time of 8-20h, more preferably 10-15h.

[0025] In the present invention, in order to obtain a stable porous material product, the method may further include sequentially drying and calcining the hydrothermal crystallization product after the hydrothermal crystallization.

[0026] More preferably, the drying conditions include: temperature of 90-150° C. and time of 11-30 h.

[0027] More preferably, the calcination conditions include: a temperature of 200-400° C., and more preferably 240-260° C. More preferably, the calcination conditions also include: a time of 2-6 hours, and more preferably 3.5-4.5 hours.

[0028] The present invention also provides a porous material with desulfurization and denitrification functions, characterized in that the porous material is prepared by the preparation method as described above;

[0029] Alternatively, the porous material comprises Si, Al and Cu, and the weight ratio of Si in terms of SiO2, Al in terms of Al2O3 and Cu in terms of CuO is 1:0.001-2.3:0.01-0.4. The weight ratio of Al in terms of Al2O3 to Si in terms of SiO2 can be 0.0001, 0.01, 0.02, 0.1, 0.12, 0.15, 0.5, 1, 1.5, 2, 2.3 or any value or range therebetween. The weight ratio of Cu in terms of CuO to Si in terms of SiO2 can be 0.02, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or any value or range therebetween.

[0030] In the porous material of the present invention, Si, Al and Cu exist in the form of oxides.

[0031] Preferably, the XRD spectrum of the porous material of the present invention has characteristic peaks at 2θ of 35.5±0.2 and 38.6±0.2.

[0032] Preferably, the porous material of the present invention is in the form of a sheet, as the sheet-shaped porous material has better dispersibility.

[0033] Preferably, the mesopore specific surface area of ​​the porous material of the present invention is 110-440 m 2 / g, more preferably 300-360m 2 / g.

[0034] Preferably, the total pore volume of the porous material of the present invention is 0.15-0.6 cm 3 / g, more preferably 0.45-0.55cm 3 / g.

[0035] Preferably, the mesopore volume of the porous material of the present invention is 0.1-0.5 cm 3 / g, more preferably 0.35-0.47cm 3 / g.

[0036] Preferably, the average pore diameter of the porous material of the present invention is 5-25 nm, more preferably 6-9 nm.

[0037] The present invention also provides a method for desulfurization and denitrification, characterized in that the method comprises: contacting the material to be desulfurized and denitrified with the porous material as described above.

[0038] There is no special requirement for the amount of the porous material. The sulfur and nitrogen adsorption capacity of each 100g of the porous material is ≥10g. Accordingly, when the porous material is used for desulfurization and denitrification, technicians in this field can determine the amount of the porous material according to the adsorption capacity. Generally, the amount of the porous material can be 2-500g per cubic meter of material.

[0039] The porous material of the present invention is suitable for various common materials containing S and N, wherein the S content of the material is ≤100 g / L, preferably 2-90 g / L, and the N content is ≤100 g / L, preferably 2-90 g / L.

[0040] The porous material of the present invention is particularly suitable for removing sulfur (including hydrogen sulfide and various organic sulfurs) and nitrogen (especially ammonia nitrogen) from organic liquids (such as naphtha). Preferably, the material is oil or gas containing sulfur and / or nitrogen.

[0041] The present invention has no special requirements on the contact conditions. Preferably, the contact conditions include: a temperature of 15-35° C. (room temperature) and a time of 0.3-1 h.

[0042] Finally, the present invention also provides the use of the porous material as described above in desulfurization and denitrification.

[0043] The present invention will be described in detail below by way of examples. The average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene (P123, CAS NO.9003-11-6) is 5800, and the long-chain alkyl trimethyl ammonium halide is CH3(CH2) 15 N + (CH3)3Cl - ; The room temperature is about "25℃".

[0044] Example 1

[0045] 0.3g aluminum hydroxide, sodium hydroxide, copper nitrate, water and P123 were mixed evenly, and tetraethyl orthosilicate was added. The prepared material was stirred at room temperature for 4 hours, and aged at 25°C for 12 hours; the aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 150°C for 1 day;

[0046] The weight of each raw material is as follows: R1 / SiO2=0.23, Al2O3 / SiO2=0.08; H2O / SiO2=11; CuO / SiO2=0.23; R2 / SiO2=0.08, where R1 and R2 represent OH, respectively. -and P123.

[0047] The obtained crystallized product was washed with water, centrifuged, and dried at 110°C for 11 hours to obtain a solid sample, and then calcined at 250°C for 4 hours to obtain a porous material. Elemental analysis (X-ray fluorescence method, refer to GB / T 30905-2014, the same below) showed that the elemental composition of the porous material was: SiO2 accounted for 72 weight%, Al2O3 accounted for 8 weight%, and CuO accounted for 20 weight%.

[0048] Example 2

[0049] 0.5 g of aluminum isopropoxide, potassium hydroxide, copper nitrate, water and long-chain alkyl trimethyl ammonium halide were mixed evenly, and then silica sol was added. The prepared material was stirred at room temperature for 5 hours and aged at 40°C for 8 hours. The aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 150°C for 2 days.

[0050] The weight of each raw material is as follows: R1 / SiO2=0.5, Al2O3 / SiO2=0.02; H2O / SiO2=100; CuO / SiO2=0.15; R2 / SiO2=0.05, where R1 and R2 represent OH, respectively. - and long chain alkyltrimethylammonium halides.

[0051] The obtained crystallized product was washed with water, centrifuged, and dried at 110°C for 20 hours to obtain a solid sample, which was then calcined at 300°C for 3 hours to obtain a porous material. Elemental analysis showed that the elemental composition of the porous material was: SiO2 accounted for 85 weight%, Al2O3 accounted for 2 weight%, and CuO accounted for 13 weight%.

[0052] Example 3

[0053] 1g of aluminum nitrate, ammonia water, copper carbonate, water and P123 were mixed evenly, and dimethylsiloxane (purchased from Sinopharm Group) was added. The prepared material was stirred at room temperature for 7 hours and aged at 45°C for 20 hours. The aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 200°C for 5 days.

[0054] The weight of each raw material is as follows: R1 / SiO2=2, Al2O3 / SiO2=1.5; H2O / SiO2=200; CuO / SiO2=0.2; R2 / SiO2=0.08, where R1 and R2 represent OH, respectively. - and P123.

[0055] The obtained crystallized product was washed with water, centrifuged, and dried at 110°C for 15 hours to obtain a solid sample, which was then calcined at 350°C for 3.5 hours to obtain a porous material. Elemental analysis showed that the elemental composition of the porous material was: SiO2 accounted for 40 weight%, Al2O3 accounted for 45 weight%, and CuO accounted for 15 weight%.

[0056] Example 4

[0057] The porous material was prepared according to the method of Example 1, except that the polyoxyethylene-polyoxypropylene-polyoxyethylene was replaced by polyethylene glycol.

[0058] Example 5

[0059] A porous material was prepared according to the method of Example 1, except that polyoxyethylene-polyoxypropylene-polyoxyethylene was not used.

[0060] Example 6

[0061] The porous material was prepared according to the method of Example 1, except that sodium hydroxide was not used.

[0062] Example 7

[0063] A porous material was prepared according to the method of Example 1, except that copper nitrate was replaced by zinc nitrate.

[0064] Example 8

[0065] A porous material was prepared according to the method of Example 1, except that copper nitrate was replaced by iron nitrate.

[0066] Comparative Example 1

[0067] A porous material was prepared according to the method of Example 1, except that copper nitrate was replaced by manganese nitrate.

[0068] Comparative Example 2

[0069] The porous material is prepared according to the traditional two-step calcination method. The specific steps are as follows:

[0070] 0.3 g of aluminum hydroxide, sodium hydroxide, water and polyoxyethylene-polyoxypropylene-polyoxyethylene are mixed evenly, and then tetraethyl orthosilicate is added, and the prepared material is stirred at room temperature for 4 hours, and aged at 25° C. for 12 hours; the aged material is loaded into a crystallization kettle with a polytetrafluoroethylene liner, and crystallized at 150° C. for 1 day, and the obtained crystallized product is washed with water, centrifuged, dried at 110° C. for 11 hours, and calcined at 250° C. for 4 hours to obtain a carrier; the carrier is impregnated with an equal volume of an aqueous solution of copper nitrate, dried at 110° C. for 11 hours, and calcined at 250° C. for 4 hours to obtain a porous material;

[0071] The weight amounts of the raw materials are the same as in Example 1.

[0072] Test Example 1

[0073] The porous materials obtained from the above examples and comparative examples were subjected to morphological analysis and structural characterization, and the results are shown in Table 1.

[0074] The morphology of the material was observed by a scanning electron microscope (SEM, model S-4800 field emission scanning electron microscope) and the X'Pert PRO X-ray diffractometer was used to measure the XRD pattern of the porous material. The mesopore specific surface area, total pore volume, mesopore volume and average pore diameter of the porous material were measured by N2 adsorption / desorption curves; the SEM photo of the porous material obtained in Example 1 is shown in FIG. Figure 1 As shown; the XRD pattern of the material obtained in Example 1 is as shown Figure 2 Although not shown, the SEM photos and XRD patterns of other embodiments are Figure 1 resemblance.

[0075] Table 1

[0076]

[0077]

[0078] Test Example 2

[0079] The porous materials obtained in the above embodiments and comparative examples are used for desulfurization and denitrification, and the specific steps are as follows: the porous material is placed in naphtha containing 30g / L hydrogen sulfide, 20g / L organic sulfide and 30g / L ammonia nitrogen (the amount of the porous material is 170g per cubic meter of naphtha), stirred at room temperature for 30 minutes, and the contents of sulfur and nitrogen in the naphtha before and after adsorption are detected with a sulfur and nitrogen analyzer, and the desulfurization rate and denitrification rate are calculated.

[0080] The results are shown in Table 2.

[0081] Table 2

[0082]

[0083]

[0084] It can be seen from the results in Table 1 that the porous material of the present invention has a similar or even higher desulfurization rate and denitrification rate than the porous material obtained by the traditional two-step method, and the preparation process is simpler. In addition, the examples using the preferred embodiments of the present invention have significantly better effects in desulfurization and denitrification.

[0085] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a porous material with desulfurization and denitrification functions, characterized in that: The preparation method comprises: hydrothermally crystallizing a crystallization raw material containing a silicon source, an aluminum source and an active metal source, wherein the weight ratio of the silicon source calculated as SiO2, the aluminum source calculated as Al2O3, and the active metal source calculated as metal oxide is 1:0.001-2.5:0.01-0.3, and the active metal source is selected from at least one of a Group VIII metal source, a Group IB metal source and a Group IIB metal source.

2. The preparation method according to claim 1, wherein The weight ratio of the silicon source calculated as SiO2, the aluminum source calculated as Al2O3 and the active metal source calculated as metal oxide is 1:0.005-2:0.02-0.

25.

3. The preparation method according to claim 1 or 2, wherein The silicon source is selected from at least one of silicon oxide, silicic acid, silicate, silicate ester and siloxane; and / or, the aluminum source is selected from at least one of aluminum alkoxide, aluminum oxide, aluminum hydroxide, aluminum salt and aluminate; And / or, the active metal source is selected from at least one of a copper source, a zinc source and an iron source.

4. The preparation method according to claim 3, wherein The silicon source is selected from at least one of silica sol, white carbon black, tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate and dimethylsiloxane; And / or, the aluminum source is selected from at least one of aluminum isopropoxide, pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum sulfate and sodium aluminate; And / or, the active metal source is selected from at least one of copper nitrate, copper carbonate and zinc nitrate.

5. The preparation method according to claim 1 or 2, wherein: The crystallization raw material also contains an alkali source in the form of OH - The weight ratio of the alkali source calculated as SiO2 to the silicon source calculated as SiO2 is less than or equal to 3, preferably 0.01-2.

5.

6. The preparation method according to claim 5, wherein: The alkali source is selected from alkali metal hydroxides and / or ammonia, more preferably at least one of sodium hydroxide, potassium hydroxide and ammonia.

7. The preparation method according to claim 1 or 2, wherein: The amount of water used in the crystallization raw material is such that the weight ratio of water to silicon source calculated as SiO2 is less than or equal to 300, preferably 0.001-280.

8. The preparation method according to claim 1 or 2, wherein: The crystallization raw material further contains an additive, wherein the weight ratio of the additive to the silicon source calculated as SiO2 is less than or equal to 0.1, preferably 0.01-0.1, more preferably 0.02-0.08; the additive is selected from a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, a structure such as CH3(CH2) n N + (CH3)3X - At least one of the long-chain alkyltrimethylammonium halides shown.

9. The preparation method according to claim 8, wherein: The average molecular weight of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is between 1500 and 12000; and / or, n=an integer of 8-18; And / or, X is Cl or Br.

10. The preparation method according to claim 1 or 2, wherein: The conditions of the hydrothermal crystallization include: a temperature of 70-220°C and a time of 0.1-7 days; Preferably, the conditions of the hydrothermal crystallization include: a temperature of 90-200° C. and a time of 0.2-5 days; Preferably, the method further comprises aging the crystallization raw material before hydrothermal crystallization, and the aging conditions include: temperature of 15-45° C. and time of 8-20 h; Preferably, the method further comprises drying and calcining the hydrothermal crystallization product in sequence after the hydrothermal crystallization; More preferably, the drying conditions include: temperature of 90-150°C and time of 11-30h; More preferably, the calcination conditions include: a temperature of 200-400° C. and a time of 2-6 hours.

11. A porous material with desulfurization and denitrification functions, characterized in that: The porous material is prepared by the preparation method described in any one of claims 1 to 10; Alternatively, the porous material comprises Si, Al and Cu, and the weight ratio of Si calculated as SiO2, Al calculated as Al2O3 and Cu calculated as CuO is 1:0.001-2.3:0.01-0.

4.

12. The porous material according to claim 11, wherein Si, Al, and Cu exist in the form of oxides; And / or, the XRD spectrum of the porous material has characteristic peaks at 2θ of 35.5±0.2 and 38.6±0.2; And / or, the porous material is in sheet form; And / or, the mesopore specific surface area of ​​the porous material is 110-440m 2 / g; And / or, the total pore volume of the porous material is 0.15-0.6cm 3 / g; And / or, the mesopore volume of the porous material is 0.1-0.5 cm 3 / g; And / or, the average pore size of the porous material is 5-25 nm.

13. A method for desulfurization and denitrification, characterized in that: The method comprises: contacting the material to be desulfurized and denitrified with the porous material according to claim 11 or 12.

14. The method according to claim 13, wherein: The amount of the porous material is 2-500 g per cubic meter of material; And / or, the S content in the material is ≤100 g / L, and the N content is ≤100 g / L; and / or, the material is oil or gas containing sulfur and / or nitrogen; And / or, the contacting conditions include: temperature of 15-35° C. and time of 0.3-1 h.

15. Use of the porous material according to claim 11 or 12 in desulfurization and denitrification.

Citation Information

Patent Citations

  • Adsorbent for gasoline desulfurization and preparation method as well as application thereof

    CN103007873A

  • Microporous-mesoporous molecular sieve containing noble metal, preparation method and application to catalytic reduction of p-nitrophenol

    CN103011189A

  • Preparation method of desulfurizing agent, desulfurizing agent and application

    CN112691651A